2013
DOI: 10.4049/jimmunol.1300062
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–Dependent IgM Memory B Cells Generated during Bacterial Infection Are Required for IgG Responses to Antigen Challenge

Abstract: Immunological memory has long considered to be harbored in B cells that express high affinity class-switched IgG. IgM-positive memory B cells can also be generated following immunization, although their physiological role has been unclear. Here we show that bacterial infection elicited a relatively large population of IgM memory B cells that were uniquely identified by their surface expression of CD11c, CD73, and PD-L2. The cells lacked expression of cell surface markers typically expressed by GC B cells, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 91 publications
13
93
0
Order By: Relevance
“…Our findings in humans give support to the above-mentioned results obtained in mice (8,9,57), suggesting that IgM + memory represents a pool of long-lasting memory cells continuously replenishing the IgG + memory pool after repeated exposure. This may be beneficial upon second encounter with a mutated form of the original pathogen, triggering their ability to re-enter the GC, switch, and acquire additional mutations, resulting in higher affinity to the mutated Ag, as also suggested in an elegant murine study describing GC-independent unmutated IgG + memory B cells (58), which, similar to the IgM memory B cells characterized in this study, are implied to confer a great flexibility to the immune system by retaining germline sequences.…”
Section: Igmsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings in humans give support to the above-mentioned results obtained in mice (8,9,57), suggesting that IgM + memory represents a pool of long-lasting memory cells continuously replenishing the IgG + memory pool after repeated exposure. This may be beneficial upon second encounter with a mutated form of the original pathogen, triggering their ability to re-enter the GC, switch, and acquire additional mutations, resulting in higher affinity to the mutated Ag, as also suggested in an elegant murine study describing GC-independent unmutated IgG + memory B cells (58), which, similar to the IgM memory B cells characterized in this study, are implied to confer a great flexibility to the immune system by retaining germline sequences.…”
Section: Igmsupporting
confidence: 90%
“…This discrepancy between the two murine studies may be related to the persistence of GC reactions in the response to particulate Ags: SRBCs in the study of Dogan et al (8), and soluble Ags in the study of Pape et al (9,56). It is relevant that we obtained similar results using a soluble Ag (TT) and a particulate Ag (D + RBCs), and that the kinetics of the memory subsets also resembled the observations of Pape et al More recently, another group studied the response to a TD Ag infection in mice and defined a subset of IgM memory B cells expressing CD11c, CD73, and PD-L2 (57). The absence of this IgM memory subset was found to abrogate the onset of IgG recall responses following a specific Ag challenge, thereby (again) supporting the idea that IgM memory plays an important role in maintaining long-term immunity.…”
Section: Igmsupporting
confidence: 80%
“…These T-bet+ CD11c+ B cells appear at the peak of the humoral immune response during infection with mouse gammaherpesvirus 68, mouse cytomegalovirus, lymphocyte choriomeningitis virus, and vaccinia. B cells with very similar phenotypic and functional characteristics have also been recently described in Ehrlichia muris infection (37). Importantly, ABCs derived during these responses secrete virus-specific IgG upon restimulation in vitro more efficiently than FO B cells from the same host, indicating recruitment of antigen-specific B cells into the ABC pool, rather than nonspecific enlargement of a bystander ABC pool.…”
Section: Abc Generation In Health and Diseasementioning
confidence: 80%
“…This altered humoral response in cGAS -/-mice was also reflected in lower levels of MSP1-specific IgG2C but not IgM (Figure 6, C and D). Expression of CD73, a marker associated with B cells that have interacted with T cells (51,52), was markedly reduced on both IgM + and IgM -memory B cells of cGAS -/-mice as compared with WT controls ( Figure 6E). We therefore concluded that ongoing infection is associated with poor GC function and memory B cell output in cGAS -/-mice.…”
Section: Persistent Infection Causes Gc Collapse and Reduction In B Cmentioning
confidence: 99%